2023
DOI: 10.3390/w15112086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drip Irrigation and Fertigation on Soil Water Dynamics and Productivity of Greenhouse Tomatoes

Abstract: The proficient supply of water and nutrients is a key factor for successful vegetable production under greenhouses. This field experiment was conducted during 2018–2019 under a completely randomized design to evaluate the effects of drip irrigation and nutrient schedule on soil water dynamics and the productivity of greenhouse tomato. The experiment consisted of two irrigation schedules, i.e., I1 (irrigation applied from week 1 to 2 on the basis of 100% pan evaporation (Epan), week 3 to 8 on the basis of 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(68 reference statements)
3
7
0
Order By: Relevance
“…Surface drip irrigation at 1.2 Epan and fertigation with 80% RDNK recorded significantly higher B:C ratio (2.37) over 0.8 Epan and fertigation with 60% RDNK (1.96) which recorded the least value. These results are in conformity withSingh et al (2023) who reported higher benefit cost ratio of 3.75 in the treatment which received 100% RDF through fertigation in tomato grown under greenhouse conditions.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Surface drip irrigation at 1.2 Epan and fertigation with 80% RDNK recorded significantly higher B:C ratio (2.37) over 0.8 Epan and fertigation with 60% RDNK (1.96) which recorded the least value. These results are in conformity withSingh et al (2023) who reported higher benefit cost ratio of 3.75 in the treatment which received 100% RDF through fertigation in tomato grown under greenhouse conditions.…”
supporting
confidence: 91%
“…These results are in accordance with Kumar et al (2010), who reported lowest yield of brinjal at 50% PE though the applied fertilizer was high. The drip irrigation at optimum level helps to maintain favorable moisture regimes, which increases the availability of water in the soil and the crop utilizes the water very effectively for the growth and development (Singh et al, 2023).…”
Section: Effect Of Drip Irrigation and Fertigation Levels On The Yiel...mentioning
confidence: 99%
See 2 more Smart Citations
“…Vegetable cultivation in Himachal Pradesh has gained significant importance owing to favourable agro-climatic conditions for growing off-season vegetables with better quality [3]. Low cost naturally-ventilated polyhouses provide a great scope in cultivation of the off-season crop such as tomato for year round supply [4]. At present, about 137 ha area in Himachal Pradesh has been brought under protected cultivation.…”
Section: Introductionmentioning
confidence: 99%